Research progress and application prospect of adipose-derived stem cell secretome in diabetes foot ulcers healing - Xiaofen Wan; Xuejun Ni; Yunjia Xie; Lu Chen; Beichen Cai; Qian Lin; Ruonan Ke; Tao Huang; Xiuying Shan; Biao Wang (Stem Cell Research & Therapy, 2024)
Abstract Diabetic foot ulcers (DFUs) are chronic wounds and one of the most common complications of diabetes, imposing significant physical and mental burdens on patients due to their poor prognosis and treatment efficacy. Adipose-derived stem cells (ADSCs) have been proven to promote wound healing, with studies increasingly attributing these beneficial effects to their paracrine actions. Consequently, research on ADSC secretome as a novel and promising alternative for DFU treatment has been extensively conducted. This article provides a comprehensive review of the mechanisms underlying refractory DFU wounds, the secretome of ADSCs, and its role in promoting wound healing in diabetes foot ulcers. And the review aims to provide reliable evidence for the clinical application of ADSC secretome in the treatment of refractory DFU wounds.